#TITLE_ALTERNATIVE# - ADE ARINI (NIM : 10209053),
The Hall Effect is a phenomenon of the rising of the voltage difference between two ends of a materialwhich is perpendicular with the applied magnetic field if the materials are given by the applied magnetic field and the electric current in the perpendicular directions. The Hall Effect is the exact method to determine the carrier concentration and the carrier mobility of a material because the carrier mobility and the Hall constant can be determined. In this experiment, the Hall Effect in Bismuth-based thermoelectric materials will be observed. Thermoelectric material is a material which can convert the heat energy to be the electrical energy, or vice versa. The performance of thermoelectric material is determined by the figure of merit value (FOM or ZT), which the ZT value is depend on the Seebeck coefficient, the electrical conductivity, thermal conductivity, and the material’s operation temperature in Kelvin. In this experiment, the other effect rising in the Hall measurement will be learned and the dependence of the Hall voltage on the electrical current and the applied magnetic field will be determined. The experiment was initiated by the literature study about the Hall effect in semiconductor and learn the other effect which is rising in the Hall measurement. The next step is create the program for supporting the data’s collectingwith running average method using LabVIEW 8.5 software. The configurations between the program and the used devices are doing and the measurement is begun. The obtained data for each configuration of the electrical current and the applied magnetic field’s polarity was manipulated to get the mixture of Hall voltage more specific and the other specific voltage as a function of the applied magnetic field and the electrical current. From the graph tendencies, it has been known that the Hall voltage’s graph form tendency as the function of the electrical current and the applied magnetic field is not linear.